Amphipathic DNA Origami Nanoparticles to Scaffold and Deform Lipid Membrane Vesicles1. (16th April 2015) - Czogalla, Aleksander; Kauert, Dominik J.; Franquelim, Henri G.; Uzunova, Veselina; Zhang, Yixin; Seidel, Ralf; Schwille, Petra
Abstract We report a synthetic biology‐inspired approach for the engineering of amphipathic DNA origami structures as membrane‐scaffolding tools. The structures have a flat membrane‐binding interface decorated with cholesterol‐derived anchors. Sticky oligonucleotide overhangs on their side facets enable lateral interactions leading to the formation of ordered arrays on the membrane. Such a tight and regular arrangement makes our DNA origami capable of deforming free‐standing lipid membranes, mimicking the biological activity of coat‐forming proteins, for example, from the I‐/F‐BAR family.